Patient characteristics and predictors of mortality among children hospitalised with tuberculosis: A six-year case series study in Uganda - Amuge, Pauline Mary; Greta, Lassance Becker; Ssebunya, Rogers Nelson; Nalumansi, Esther; Adaku, Alex; Juma, Michael; Jay, Brooks Jackson; Kekitiinwa, Adeodata Rukyarekere; Elyanu, Peter James; Wobudeya, Eric; Robert, Blount (PLoS ONE, 2024)
Background The high case-fatality rates among children with tuberculosis (TB) are reportedly driven by in-hospital mortality and severe forms of TB. Therefore, there is need to better understand the predictors of mortality among children hospitalised with TB. We examined the patient clinical profiles, length of hospital stay from date of admission to date of final admission outcome, and predictors of mortality among children hospitalised with TB at two tertiary hospitals in Uganda. Methods We conducted a case-series study of children below 15 years of age hospitalised with TB, from January 1st, 2016, to December 31st, 2021. Convenience sampling was done to select TB cases from paper-based medical records at Mulago National Referral Hospital (MNRH) in urban Kampala, and Fort Portal Regional Referral Hospital (FRRH) in rural Fort Portal. We fitted linear and logistic regression models with length of stay and in-hospital mortality as key outcomes. Results Out of the 201 children hospitalised with TB, 50 were at FRRH, and 151 at MNRH. The male to female ratio was 1.5 with median age of 2.6 years (Interquartile range-IQR 1–6). There was a high prevalence of HIV (67/171, 39%), severe malnutrition reported as weight-for-age Z-score <-3SD (51/168, 30%). Among children with pulmonary TB who initiated anti-tuberculosis therapy (ATT) either during hospitalisation or within seven days prior to hospitalisation; cough (134/143, 94%), fever (111/143, 78%), and dyspnoea (78/143, 55%) were common symptoms. Children with TB meningitis commonly presented with fever (17/24, 71%), convulsions (14/24 58%), and cough (13/24, 54%). The median length of hospital stay was 8 days (IQR 5–15). Of the 199 children with known in-hospital outcomes, 34 (17.1%) died during hospitalisation. TB meningitis was associated with in-hospital mortality (aOR = 3.50, 95% CI = 1.10–11.17, p = 0.035), while male sex was associated with reduced mortality (aOR = 0.33, 95% CI = 0.12–0.95, p = 0.035). Hospitalisation in the urban hospital predicted a 0.48-day increase in natural log-transformed length of hospital stay (ln-length of stay) (95% CI 0.15–0.82, p = 0.005), but not age, sex, HIV, malnutrition, or TB meningitis. Conclusions In-hospital mortality was high, and significantly driven almost four times higher by TB meningitis, with longer hospital stay among children in urban hospitals. The high in-hospital mortality and long hospital stay may be reduced by timely TB diagnosis and treatment initiation among children.